2013
DOI: 10.1002/mrm.24785
|View full text |Cite
|
Sign up to set email alerts
|

Mapping mean and fluctuating velocities by Bayesian multipoint MR velocity encoding‐validation against 3D particle tracking velocimetry

Abstract: Accelerated Bayesian multipoint MR velocity encoding has been demonstrated to be accurate for assessing mean and fluctuating velocities against the reference standard particle tracking velocimetry. The MR method holds considerable potential to map velocity vector fields and turbulent kinetic energies in clinically feasible exam times of <15 min.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 34 publications
0
37
1
Order By: Relevance
“…In the preliminary study, the Siemens 4D PC-MRI sequence was found to eliminate TKE along the slice-direction because the sequence has nonsymmetric encoding around 2 axes. Therefore, we note that TKE in the present study could be lower in comparison with other studies that used other MR scanners5960.…”
Section: Methodscontrasting
confidence: 72%
“…In the preliminary study, the Siemens 4D PC-MRI sequence was found to eliminate TKE along the slice-direction because the sequence has nonsymmetric encoding around 2 axes. Therefore, we note that TKE in the present study could be lower in comparison with other studies that used other MR scanners5960.…”
Section: Methodscontrasting
confidence: 72%
“…PIV measurements and the validation experiments were restricted to flow in a single plane. However, the present phantom setup is compatible with and can be extended to three‐dimensional laser techniques such as PTV, as recently used by Knobloch et al .…”
Section: Discussionmentioning
confidence: 99%
“…100 Since blood flow in the aorta is intricate, plenty of velocity measurements both in vitro and in vivo have been performed in the past years using different tools such as hot film, Doppler ultrasound, three-dimensional particle tracking velocimetry (3D-PTV) and phase contrast magnetic resonance imaging (PC-MRI). 26,35,48,49,66,81,82 The studies demonstrated that flow pattern in the ascending aorta was skewed and helical flow predominated in areas from the ascending aorta to the aortic arch in the systole. Kilner et al firstly used the three-directional phase contrast cine magnetic resonance velocity mapping to investigate the multidirectional flow velocities in the human aorta.…”
Section: Helical Flow In Human Vasculaturementioning
confidence: 97%